2020
DOI: 10.1126/sciadv.abb2788
|View full text |Cite
|
Sign up to set email alerts
|

Seabird establishment during regional cooling drove a terrestrial ecosystem shift 5000 years ago

Abstract: The coastal tussac (Poa flabellata) grasslands of the Falkland Islands are a critical seabird breeding habitat but have been drastically reduced by grazing and erosion. Meanwhile, the sensitivity of seabirds and tussac to climate change is unknown because of a lack of long-term records in the South Atlantic. Our 14,000-year multiproxy record reveals an ecosystem state shift following seabird establishment 5000 years ago, as marine-derived nutrients from guano facilitated tussac establishment, peat productivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Shell middens along the Beagle Channel indicate human occupation of the coastline during at least the last 6,500 years, with a stable marine biota (Estévez et al, 2001). A 14,000 year multiproxy record of seabird guano and tussac grass (Poa flabellata) in the Falkland Islands showed an abrupt establishment of P. flabellata and seabird colonies ~5000 year BP (Groff et al, 2020), which, in turn, could have meant massive nutrient inputs for kelp growth. In turn, seabirds like the kelp gull Larus dominicanus can forage on bivalves growing on kelp blades like Gaimardia trapesina (Friedlander et al, 2020;Hockey, 1988).…”
Section: Anthropogenic Changes and Kelp Persistencementioning
confidence: 99%
“…Shell middens along the Beagle Channel indicate human occupation of the coastline during at least the last 6,500 years, with a stable marine biota (Estévez et al, 2001). A 14,000 year multiproxy record of seabird guano and tussac grass (Poa flabellata) in the Falkland Islands showed an abrupt establishment of P. flabellata and seabird colonies ~5000 year BP (Groff et al, 2020), which, in turn, could have meant massive nutrient inputs for kelp growth. In turn, seabirds like the kelp gull Larus dominicanus can forage on bivalves growing on kelp blades like Gaimardia trapesina (Friedlander et al, 2020;Hockey, 1988).…”
Section: Anthropogenic Changes and Kelp Persistencementioning
confidence: 99%
“…Lacustrine environments (i.e., standing water) are preferred, as the sediments tend to accumulate chronologically with minimal mixing, in contrast to those in fluvial environments (i.e., running water) (Smol, 2008). There is also a limited but growing body of literature using similar paleolimnological approaches on peat (Outridge et al, 2016;Davidson et al, 2018;Groff et al, 2020), directly from nests (Burnham et al, 2009), and on guano deposits themselves (Nocera et al, 2012;Gallant et al, 2020Gallant et al, , 2021. Next, the sample is collected using a sediment corer, which, in its simplest form, is a tube inserted into the sediment to retrieve an undisturbed vertical profile of sediment [see Glew et al (2001) for a detailed overview].…”
Section: What Is Paleolimnology?mentioning
confidence: 99%
“…However, the paleolimnological techniques described in this review are not limited to bodies of water and can be expanded to peatlands and directly to guano deposits. For example, recent work has effectively used peat deposits, which may occur in locations without bodies of water, to track various seabirds using the North Water polynya in northwest Greenland (Outridge et al, 2016;Davidson et al, 2018) and seabirds nesting on the Falkland Islands (or Islas Malvinas in Argentina) (Groff et al, 2020). Similarly, some species produce geochronological accumulations of wastes based on their roosting behavior.…”
Section: Availability Of Sampling Locationsmentioning
confidence: 99%
“…For example, Groff et al. ( 19 ) recently showed that the expansion of tussock grasslands on the Falkland Islands was regulated by the establishment of seabird colonies that enhanced transfers of nutrients from marine to terrestrial ecosystems. Second, bone frequency may carry a complex relationship to megafaunal population abundance, given the vagaries of collection efforts and given that past environmental change may alter the likelihood of bone preservation.…”
Section: Implications For Contemporary Biodiversity Managementmentioning
confidence: 99%